"A Description of the Interior of the Home of Mr. and Mrs. Monte Drake in the Community of Lourdes on the West Coast of Newfoundland, Bay St. George" - Drake, Elaine Perpetua (1978)
Dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial. -- Memorial University folklore student term paper. Deuxième d'une serie de trois dissertations faisant partie de la même accession - Associée aux photos P4720-P4729 -- Second in a series of three term papers comprising one accession - associated with photos P4720-P4729